Impact of bisoprolol transdermal patch on early recurrence during the blanking period after atrial fibrillation ablation. Issue 3 (4th May 2021) - Suzuki, Yuya; Kuroda, Masaru; Fujioka, Tomoo; Kintsu, Masayuki; Noda, Tsubasa; Matsumoto, Akinori; Kawata, Masahito
Abstract: Background: Early recurrences of atrial arrhythmias (ERAAs) after ablation may require therapeutic intervention. The optimal medical therapy that prevents ERAAs requires clarification. This study aimed to compare the incidence of ERAAs between patients who received or did not receive bisoprolol transdermal patches (BTPs) at 3 months postablation. Methods: This single‐center retrospective study enrolled 203 consecutive patients with paroxysmal atrial fibrillation (AF) who had undergone their first ablation, comprising 59 in the BTP group and 144 in the non‐BTP group. Follow‐up assessments were conducted monthly for 3 months. We evaluated the incidence of ERAAs. Results: During the initial 1‐week observational period, the rate of ERAAs was lower in the BTP group (5.0%) than that in the non‐BTP group (18.8%) ( P  = .013). At 3 months postablation, the rate of ERAAs was lower in the BTP group (6.8%) than that in the non‐BTP group (25.7%) ( P  = .002). The cumulative freedom from ERAAs was significantly lower in the BTP group than in the non‐BTP group (log‐rank: P  = .003). Administering BTPs was an independent factor that protected against ERAAs (odds ratio 0.181, [95% confidence interval 0.059‐0.559], P  = .003). Conclusion: BTPs may prevent ERAAs after ablation. Abstract : The patients who were administered bisoprolol transdermal patches (BTPs) immediately after atrial fibrillation (AF) ablation showed significant reductions in the incidence of early recurrence of atrial arrhythmias (ERAAs) compared with the patients who were not administered BTPs. The efficacy of BTPs at preventing ERAAs was confirmed not only immediately after ablation, but also during the short period after AF ablation.